Rationale and design of ‘discontinuing statins in multimorbid older adults without cardiovascular disease (STREAM)’: study protocol of a randomised non-inferiority clinical trial - Mirjam Christ-Crain; Manuel R Blum; Philipp Schuetz; Luise Adam; Elisavet Moutzouri; Martin Feller; Drahomir Aujesky; Sven Trelle; Nicolas Rodondi; Marie Méan; Rosalinde K E Poortvliet; Jürg-Hans Beer; et al. (BMJ Open)
Introduction Statins are among the most widely used drugs. While they are effective for primary and secondary prevention of cardiovascular (CV) disease in middle-aged subjects, their benefits for prevention in older adults (aged ≥70 years) without CV disease are uncertain, particularly for those with multimorbidity. Statin side effects and drug interactions are common in older patients and may negatively impact quality of life. To date, the only randomised controlled trial (RCT) investigating statin discontinuation in older adults has demonstrated no difference in survival but did note a small improvement in quality of life for those who discontinued statins. However, this trial exclusively enrolled patients with a life expectancy <1 year. Therefore, the present RCT aims to assess the safety and potential benefits of statin discontinuation in primary prevention for the ever-growing population of multimorbid older adults.Methods and analysis This study is a multicentre, randomised, non-inferiority trial conducted in both inpatient and outpatient settings in Switzerland, France and the Netherlands, targeting patients using statins for primary prevention. 1800 participants are randomly assigned 1:1 to either discontinue (intervention arm) or continue (control arm) statin therapy. The primary objective is to compare the primary composite endpoint of major CV events (non-fatal myocardial infarction or non-fatal ischaemic stroke) and all-cause death between the control and intervention groups over a follow-up duration of up to 48 months. We hypothesise that discontinuing statins does not result in shorter event-free survival, with a non-inferiority margin set at 5.2 weeks over a 2-year observation period. Secondary objectives are to compare patient-centred outcomes (health-related quality of life, muscle pain symptoms, falls and sarcopenia) and all-cause death, non-CV death, major CV events and coronary and peripheral artery revascularisation. The study is open-labelled, with blinded outcome adjudication of the primary endpoints.Ethics and dissemination The trial protocol has received approval from the local ethics committees in Switzerland, France and the Netherlands. Results will be published in a peer-reviewed journal.Trial registration number Clinicaltrials.gov: NCT05178420; BASEC (Swiss Ethics Commission): 2021-01513; FOPH (Swiss national portal): SNCTP000005172; Netherlands Trial Register: NL83907.058.23; France Trial Register: 22.04747.000158– IDRCB 2022-A02481-42.